Manajemen Profesi Guru Abad 21 - Indra Indra; Firman Hadi; Indah Mayasari; Siti Arafah E.N; Aisyah Oktaviana; Melin Andilla (Peneliti.net, 2022)
This paper aims to find out how the development of teacher professionalism is through the performance of teachers in education units at SMP Negeri 35 Medan. This research is a field research (filed research) which is descriptive qualitative, with the aim to be achieved by the researcher is a factual description by collecting The data that will be used are observations, interviews, and documentation obtained directly in the field. The results of research on the development of teacher professionalism through teacher performance in education units at SMP Negeri 35 Medan were carried out with several programs and efforts, namely conducting education and training by carrying out subject teacher meetings (mgmp). teacher professional development in Indonesia in various aspects, namely aspects of teaching career development, aspects of teaching career development and aspects of professional development, First; Teacher education qualification improvement program; Second; Equalization and certification program; Third; Competency-based integrity training program; Fourth; Conduct research. The end of this study is that the development of teacher professionalism through teacher performance is carried out in the school itself by paying attention to the weaknesses of the teacher to become a material for introspection for future improvements. However, the development of teacher professionalism at SMP Negeri 35 Medan is not optimal but still requires guidance and direction in order to achieve the program from relevant stakeholders, both the government and education observers.